The key role of sample analysis in Fukushima Dai-Ichi decommissioning, debris management, and accident progression investigation - Zubekhina, Bella; Pshenichnikov, Anton; Nagae, Yuji; Kurata, Masaki (Frontiers in Nuclear Engineering, 2023)
The review outlines the up-to-date situation with an analysis of the U-bearing samples from Fukushima Daiichi Nuclear Power Station (1F). The experience gained after previous severe nuclear accidents in the field of fuel debris analysis and utilization of the results is summarized. Current methods of 1F sample analysis and the main results are presented with a discussion on future strategies of fuel debris analysis and 1F decommissioning needs.